Oxidation resistance of bulk plasma-facing tungsten alloys. (May 2018) - Klein, F.; Wegener, T.; Litnovsky, A.; Rasinski, M.; Tan, X.Y.; Gonzalez-Julian, J.; Schmitz, J.; Bram, M.; Coenen, J.W.; Linsmeier, Ch.
Highlights: Optimization of field assisted sintering technology for W–Cr–Y alloys. Studies on the oxidation resistance of bulk W–Cr–Y alloys at 1273 K for up to 3 weeks. Sublimation rate of 1 × 10 − 6 mg cm − 2 s − 1 . measured, estimation of radiological hazards. Suppression of sublimation for 2 days at 1273 K in synthetic air. Abstract: Tungsten (W) currently is the main candidate as plasma-facing armour material for the first wall of future fusion reactors, like DEMO. Advantages of W include a high melting point, high thermal conductivity, low tritium retention, and low erosion yield. However, in case of an accident, air ingress into the vacuum vessel can occur and the temperature of the first wall can reach 1200 K to 1450 K due to nuclear decay heat. In the absence of cooling, the temperature will remain in that range for several weeks. At these temperatures the radioactive tungsten oxide volatilizes. Therefore, 'smart' W alloys are developed that aim to preserve the properties of W during plasma operation coupled with suppressed tungsten oxide formation in case of an accident. This study focusses on oxidation studies at 1273 K of samples produced by mechanical alloying followed by field assisted sintering. In a first step the sintering is optimized for tungsten (W) – chromium (Cr) -yttrium (Y) alloys. It is shown that the best oxidation resistance is achieved with submicron grain sizes. This yields a closed, protective oxide layer. In a second step the influence of the grinding process during sample preparation is analysed. It is shown that scratches initiate failure of the protective oxide. In a third step the oxidation and sublimation is measured for weeks – for the first time the sublimation is directly measured in order to determine the potential hazard in comparison to pure W. It is shown that the oxidation is suppressed in comparison to pure W. However, sublimation at a rate of 1 × 10 − 6 mg cm − 2 s − 1 starts after a few days. Nevertheless, the progess in smart alloys is evident: sublimation is delayed by about two days and complete mechanical destruction of the first wall is avoided.